The Degree of Applying Accountability Principles in Public & Private Universities in Jordan: A Comparative Study BetweenYarmouk University and Jerash University - Ahmed Malkawi; Kamil Al-Otoum (European Scientific Journal, ESJ, 2017)
The study aimed to identify the status of applying the principles of accountability in the public and private universities in Jordan. This was done by comparing between Yarmouk University and Jerash University from the perspective of the employees. The study sample consisted of 250 faculty members and one administrator at Yarmouk University and Jerash University. The questionnaire was used as a tool for data collection. The study reached several conclusions, most notably of which include the presence of statistically significant differences in the reality of applying the accountability principles at universities in general, and in the administrative, and academic fields. This, however, is dependent on the variable of the university in favor of Jerash University. The study concluded on a number of recommendations most important of which is the necessity of activating the accountability mechanisms and tools in three areas: administrative, and academic areas of public universities in a higher degree. It also includes a commitment with unified criteria of accountability to ensure the maintenance of an acceptable level of justice and transparency.